2023
DOI: 10.1039/d3cc00881a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed indium-mediated reductive aromatic C–H allylation of N-benzylsulfonimides with allyl esters

Abstract: An unprecedented reductive aromatic C−H allylation reaction of benzyl electrophiles with allyl electrophiles has been established. A range of N-benzylsulfonimides smoothly participated in the palladium-catalyzed indium-mediated reductive aromatic C−H allylation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In recent years, both benzyl and arylammonium salts have been explored as promising electrophiles for reductive cross-coupling reactions. Benzyltrimethylammonium salts have been reported to participate in nickel-catalyzed manganese- or zinc-mediated reductive cross-coupling reactions with CO 2 , , aryl sulfonates, vinyl acetates, and phenyl benzoates (Scheme a) . Yu and co-workers have developed visible-light-driven cross-electrophile couplings of benzyltrimethylammonium salts with aldehydes, ketones, CO 2 , and nitriles in the absence of external reductants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, both benzyl and arylammonium salts have been explored as promising electrophiles for reductive cross-coupling reactions. Benzyltrimethylammonium salts have been reported to participate in nickel-catalyzed manganese- or zinc-mediated reductive cross-coupling reactions with CO 2 , , aryl sulfonates, vinyl acetates, and phenyl benzoates (Scheme a) . Yu and co-workers have developed visible-light-driven cross-electrophile couplings of benzyltrimethylammonium salts with aldehydes, ketones, CO 2 , and nitriles in the absence of external reductants.…”
mentioning
confidence: 99%
“… a (a) Reductive cross-coupling reactions of benzyltrimethylammonium salts. (b) Reductive cross-coupling reactions of aryltrimethylammonium salts. , (c) Highly site-selective C–N bond cleavage for the reductive cross-coupling reactions of arylbenzylammonium salts (this work). …”
mentioning
confidence: 99%
“…8 In 2023, Tian and co-workers disclosed the reductive aromatic C−H allylation of an N-(2thienylmethyl)sulfonimide with an allylammonium salt in 25% yield (Scheme 1b). 9 To extend the application of allylammonium salts to the formation of C(sp 3 )−C(sp 3 ) bonds through cross-electrophile coupling, we initiated our investigation on a possible reductive cross-coupling reaction of allylammonium salts with alkyl electrophiles (Scheme 1c). After screening a number of nickel sources, ligands, reductants, additives, and solvents, we found that the model reaction of cinnamylammonium bromide 1a with 1-iodocyclohexane (2a) proceeded well in the presence of NiCl 2 •6H 2 O (10 mol %), SIMes•HCl (15 mol %), zinc power (4 equiv), and TBAI (1 equiv).…”
mentioning
confidence: 99%
“…In 2018, Yu and co-workers reported the photoredox-catalyzed reaction of an allylammonium salt with carbon dioxide, delivering two isomeric β,γ-unsaturated carboxylic acids with 1:1.25 linear/branched selectivity (Scheme a) . In 2023, Tian and co-workers disclosed the reductive aromatic C–H allylation of an N -(2-thienylmethyl)­sulfonimide with an allylammonium salt in 25% yield (Scheme b) . To extend the application of allylammonium salts to the formation of C­(sp 3 )–C­(sp 3 ) bonds through cross-electrophile coupling, we initiated our investigation on a possible reductive cross-coupling reaction of allylammonium salts with alkyl electrophiles (Scheme c).…”
mentioning
confidence: 99%